Collaboration with JINR as Key for Nuclear Physics Development in Ukraine - Grinyov, B.V.; Bulavin, L.A.; Soloviov, D.V.; Stadnik, P.O. (Science and Innovation, 2024)
Introduction. Today, the Joint Institute for Nuclear Research (JINR) is a kind of scientific and technical framework for Ukrainian nuclear researchers who are directly involved in conducting the cutting-edge nuclear physics experiments. Problem Statement. An important aspect of international cooperation for the Ukrainian researchers in the field of nuclear physics and materials science is to consolidate scholarly research, engineering, and financial resources of countries for creating international research organizations and implementing large-scale projects in modern science and technology. Purpose. Analysis of the factors that contribute to the development of nuclear physics and research in related disciplines in Ukraine, involvement of Ukrainian researchers in international research processes, and assessment of the future prospects. Materials and Methods. Analysis of scholarly research trends in the Joint Institute for Nuclear Research (JINR) and review of achievements of Ukrainian researchers, in particular, young researchers, in implementation of international projects in nuclear physics and related disciplines. Results. The background of nuclear physics research in Ukraine, the way of international cooperation development, and its impact on education and training of researchers have been analyzed. The examples of research results of Ukrainian nuclear physicists have been given. The cooperation of Ukrainian R&D organizations and companies with JINR has been shown to have a positive effect on creative and innovative processes, including the development and study of new high-tech materials. Conclusions. Collaboration with JINR gives Ukrainian researchers access to modern methods of physical research and unique equipment at leading international R&D centers, while planning and implementing large-scale experiments in nuclear physics, and enables studying the problems of the Universe. Teachers, students, and schoolchildren from Ukraine have additional opportunities to work with the cutting-edge methods, modern equipment and innovative approaches in the field of science and technology.